2016
DOI: 10.2196/jmir.5702
|View full text |Cite
|
Sign up to set email alerts
|

Professional Use of Social Media by Pharmacists: A Qualitative Study

Abstract: BackgroundSocial media is frequently used by consumers and health care professionals; however, our knowledge about its use in a professional capacity by pharmacists is limited.ObjectiveOur aim was to investigate the professional use of social media by pharmacists.MethodsIn-depth semistructured interviews were conducted with practicing pharmacists (N=31) from nine countries. Interviews were recorded, transcribed verbatim, and thematically analyzed.ResultsWikipedia, YouTube, and Facebook were the main social med… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 38 publications
1
29
0
1
Order By: Relevance
“…Social listening is an established and efficient way to study online communities [ 19 ]. Previous studies have used Facebook to examine the social media activity of clinicians and pharmacists [ 20 , 21 ]; to evaluate Facebook groups focused on diabetes and explore the information that patients request, the unsolicited information that is provided, and the nature of the virtual communities that congregate on Facebook [ 22 ]; and to examine risk perceptions of obesity among social media users [ 23 ]. We build on this methodology by using responses to the VR video posted on Facebook as a virtual focus group to characterize public knowledge, attitudes, beliefs, and preferences about the use of VR in health care.…”
Section: Methodsmentioning
confidence: 99%
“…Social listening is an established and efficient way to study online communities [ 19 ]. Previous studies have used Facebook to examine the social media activity of clinicians and pharmacists [ 20 , 21 ]; to evaluate Facebook groups focused on diabetes and explore the information that patients request, the unsolicited information that is provided, and the nature of the virtual communities that congregate on Facebook [ 22 ]; and to examine risk perceptions of obesity among social media users [ 23 ]. We build on this methodology by using responses to the VR video posted on Facebook as a virtual focus group to characterize public knowledge, attitudes, beliefs, and preferences about the use of VR in health care.…”
Section: Methodsmentioning
confidence: 99%
“…Despite the available opportunities for pharmacists to educate patients on medications and disease states using social media, this is an infrequent occurrence. A qualitative survey of 31 pharmacists across nine countries found that none of the pharmacists were delivering any type of services via social media despite recognizing the potential of social media . Deterrents for engaging patients on social media included patient privacy concerns, lack of reimbursement for providing education online, preference for face‐to‐face interactions, and need to acquire new skills to engage with social media.…”
Section: Opportunitiesmentioning
confidence: 99%
“…A qualitative survey of 31 pharmacists across nine countries found that none of the pharmacists were delivering any type of services via social media despite recognizing the potential of social media. 5,6 Deterrents for engaging patients on social media included patient privacy concerns, lack of reimbursement for providing education online, preference for face-to-face interactions, and need to acquire new skills to engage with social media. Additionally, the legality of the pharmacist-patient relationship through social media remains untested and the pharmacists' "duty to warn" may still apply if the pharmacist has a legitimate relationship with the patient.…”
Section: Patient Carementioning
confidence: 99%
See 1 more Smart Citation
“…Our analysis would suggest that updating these Wikipedia articles with these Cochrane Reviews would improve their quality on the basis of Wikipedia's own rating system. In light of the multi-societal disposition to consult the Internet for health-related information 19,[45][46][47][48][49] and the widely prevalent use of Wikipedia specifically to fulfil these information needs, 11,19,23,50,51 its value as a free source of knowledge, and the importance of ensuring that this knowledge reflects highquality scientific evidence, are indisputable. As the most referenced scientific journal among medical Wikipedia articles, 37 the Cochrane Database of Systematic Reviews is an invaluable source of the secondary research cited on Wikipedia.…”
Section: Discussionmentioning
confidence: 99%